THE DIFFERENT USES OF UKEN AND TOA DIALECT ON GAYO LANGUAGE - Hayatullah, Hayatullah; Siwi, Purwanto (Universitas Islam Sumatera Utara, 2024)
The differences between the Uken and Toa dialects are easy to identify in the daily conversations of the speakers. Speakers of these two dialects are still easy to understand each other. The differences occur in several vocal sounds, intonation, some vocabulary, as well as some greetings in everyday dialogue. The aim to be achieved in this research is to find out the differences between the Gayo Uken and Toa dialects. The research method used in this study is a descriptive qualitative method. The differences in conversation between the Uken and Toa people can be seen in terms of their pronunciation when interacting. Besides, there are also slight differences in vocabulary between the two dialects. The differences between the two Gayo dialects occur in the vowel phoneme change and consonant one. The variations of the phonemes used in both dialects stay at the same meaning, but they are pronounced differently. As a result, based on the pronunciation of the Uken and Toa dialects spoken by the community, there are many phoneme variations. Every spoken word produces dissimilarities in vowel phonemes and consonant phonemes.